An application of factor analysis to assess the influences of digital marketing on the brand building - Aziz, Khanda Gharib; Rafiq, Rebin; Muhamad, Hokar (Raden Intan State Islamic University of Lampung, Indonesia, 2023)
This study highlights how digital marketing has made people know more about brands and promote brands in the market through technology. The study focuses on the effects of digital marketing on the branding of a specific product, the Apple brand (iPhone). With a special focus on the factors that make the iPhone brand more popular than other brands. The purpose of this study is to investigate the concept of digital marketing and examine the effects of digital marketing on brand creation, as well as to investigate the factors that make Apple's mobile phones more popular than other brands. This study helps to identify the relationship between digital marketing and brand building in the Kurdistan Region. Through quantitative research methodology, judicial sampling was used to collect data from 184 respondents, the study targeted people who use iPhones. The scope of this study was conducted in Halabja, Sulaimani and Erbil through questionnaire forms in South Iraqi Kurdistan. The findings show that digital advertising is a significant factor in differentiating the iPhone brand, increasing brand awareness and enhancing familiarity with product variety. The study suggests that businesses should incorporate digital marketing strategies into their marketing mix to build their brands effectively.